Managing the Transition towards Circular Metabolism: Living Labs as a Co-Creation Approach - Amenta, Libera (2019)
Resource consumption and related waste production are still rapidly increasing all over the world, leading to social and environmental challenges and to the production of the so-called ‘wastescapes’. Peri-urban areas—in-between urban and rural territories—are particularly vulnerable and prone to develop into wastescapes because they are generally characterised by mixed functions and/or monofunctional settlements, as well as by fragmentation in a low-density territory that is often crossed by large infrastructure networks. Moreover, peri-urban areas are generally the selected locations for the development of plants for waste management. In this way, they are crossed by waste flows of a different nature, in a landscape of operational infrastructures and wasted landscapes. Implementing Circular Economy (CE) principles, interpreting waste and wastescapes as resources, is a way to significantly reduce raw material and (soil) resource consumption, improving cities’ metabolism. A circular approach can positively affect the spatial, social and environmental performances of peri-urban areas. However, the transition towards a CE presents many challenges. This article outlines an approach to address these challenges, presenting a co-creation process among researchers, experts and stakeholders within Living Labs (LLs) processes. LLs are physical and virtual spaces, aiming at the co-creation of site-specific eco-innovative solutions (EIS) and strategies. In the LLs, public–private–people partnerships are developed by applying an iterative methodology consisting of five phases: Co-Exploring, Co-Design, Co-Production, Co-Decision, and Co-Governance. This article presents a case study approach, analysing the co-creation methodology applied in two peri-urban living labs, located in the Metropolitan Areas of Naples (Italy) and Amsterdam (The Netherlands), within REPAiR Horizon2020 research project.